Adequação de cátions no solo para produção e qualidade do melão - Oliveira, Líssia Letícia de Paiva (Universidade Federal Rural do Semi-Árido, 2019)
In the semiarid region of Brazil, especially in Chapada do Apodi, the cambisols in potential proportions of calcium and magnesium (in smaller quantity), due to the calcareous origin, besides neutral to alkaline pH. The productivity and quality of the world's fruits are negatively affected in many cases due to the imbalance between soil soil types. Thus, a research was developed with the objective of identifying the cationic relations of the soil that best correlate with the production and quality indicators of the melon fruits. Two experiments were performed sequentially in pots under vegetation conditions in Mossoró - RN. Thirteen randomized blocks with 4 repetitions were adopted. For the dosage of salts were forced 5: Ca (1:34; 1:27; 1:21; 1:16 and 1:9) Mg of the ratio: Ca (1:11; 1:9; 1:7; 1:5 and 1:3), no soil, combined by a matrix called double-square. The used crop was melon, cultivated in medium texture soil, drip irrigated. The blocks were applied in foundation fertilization. How they were evaluated during the crop cycles were: vegetative development of the plant, soil analysis during the fruiting phase and end of the cycle, weekly analysis of the soil solution, nutrient concentration in the diagnostic leaf, nutrient accumulation in the plant phase. fruiting and end-of-cycle, total and commercial yield per plant, and to evaluate fruit quality by pulp therapists, pulp thickness, soluble solids content, pulp pH, ripeness index and titratable total acidity. A. An order of nutrient accumulation at the end of the cycle without experiment I was: K>Ca>N>Mg>P and Zn>Fe>Mn, and without experiment II: K>Mg>N>P>Ca and Fe>Zn>Mn. The fertilization for cationic adequacy in the soil did not influence the characteristics of production and postharvest quality of the fruits. Irrigation water from the water aquifer is a source of fertigation to suppress the calorie of nutrients K and Mg without cationic ratio correction fertilization.
Keywords: Cucumis melo L.; Magnésio; Nutrição mineral; Cucumis melo L.; Soil fertility; Fruit yield; Nutrientes; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO